2007
DOI: 10.1007/s10803-007-0459-0
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sensory Processing Patterns and Behavioural Responsiveness in Autistic Disorder: A Pilot Study

Abstract: Sensory processing (SP) difficulties have been reported in as many as 95% of children with autism, however, empirical research examining the existence of specific patterns of SP difficulties within this population is scarce. Furthermore, little attention has been given to examining the relationship between SP and either the core symptoms or secondary manifestations of autism. In the current study, SP patterns in children with autistic disorder (AD) were investigated via a caregiver questionnaire and findings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
212
1
15

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(246 citation statements)
references
References 26 publications
18
212
1
15
Order By: Relevance
“…It has been suggested that children with ASD who experience sensory processing abnormalities may also experience more repetitive behaviours (e.g. Chen, Rodgers, & McConachie, 2009;Baker et al, 2008). Repetitive behaviours may be functional in regulating arousal levels for children with ASD who experience sensory processing abnormalities (e.g.…”
Section: Exploring the Relationship Between Sensory Processing And Rementioning
confidence: 99%
“…It has been suggested that children with ASD who experience sensory processing abnormalities may also experience more repetitive behaviours (e.g. Chen, Rodgers, & McConachie, 2009;Baker et al, 2008). Repetitive behaviours may be functional in regulating arousal levels for children with ASD who experience sensory processing abnormalities (e.g.…”
Section: Exploring the Relationship Between Sensory Processing And Rementioning
confidence: 99%
“…The model also shows how imitation training (e.g., [7], [13]) can strengthen the empathic responses. Moreover, it shows that when enhanced sensory processing sensitivity [1] occurs (e.g., as an innate factor), the natural learning process is obstructed by avoidance behaviour to downregulate the dysproportional arousal [9].…”
Section: Discussionmentioning
confidence: 99%
“…200-203, [12], [16]) for context c, stimulus s and body state b; they provide control for the agent's execution of (prepared) actions, such as expressing body states or communications, or regulation of the gaze. Here the context c can be an agent B, which can be another agent (self-other distinction), or the agent self, or c can be sens which denotes enhanced sensory processing sensitivity: a trait which occurs in part of the population, and may affect social behaviour (e.g., [1,4]). One reason why some children do not obtain a sufficient amount of experiences to shape their mirror neuron system, is that they tend not to look at other persons due to enhanced sensory processing sensitivity for face expressions, in particular in the region of the eyes; e.g., [4,15].…”
Section: The Adaptive Agent Model Based On Hebbian Learningmentioning
confidence: 99%
See 2 more Smart Citations